Information System Analysis of Assistance Services for Persons with Social Welfare Problems Based on Android Towards Smart City - ., Arman; ., Alang; Malago, Yusrianto (KnE Social Sciences, 2020)
The purpose of this research is to find out and develop an analysis of information system assistance services for people with problems based on Android-based social welfare towards smart cities. The object of this study is the Procurement Information System and Distribution of Assistance to People with Social Welfare Problems (PMKS) in social offices and Android-based workforce in Gorontalo. Stage one involved data collection. The second stage, involved analysing the data and the problems. The third stage was to create a design model, output design, input design, database design and technology design. Keywords: Information system analysis, social welfare, smart city